2008
DOI: 10.1002/jnr.21605
|View full text |Cite
|
Sign up to set email alerts
|

YFa, a chimeric opioid peptide, induces kappa‐specific antinociception with no tolerance development during 6 days of chronic treatment

Abstract: Our previous study showed that YGGFMKKKFMRFamide (YFa), a chimeric peptide of Met-enkephalin, and Phe-Met-Arg-Phe-NH2 induced naloxone-reversible antinociception and attenuated the development of tolerance to morphine analgesia. In continuation, the present study investigated which specific opioid receptors-mu, delta or kappa-mediate the observed YFa antinociception pharmacologically using specific antagonists and whether chronic administration of YFa at 26.01 micromol/kg per day induces tolerance and its effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 31 publications
0
10
0
Order By: Relevance
“…A dynorphin A-(1-7) analog stabilized to metabolism, SK-9709 (Figure 1), also exhibited antinociceptive activity following systemic (s.c.) administration (Table 2) [19]. In addition, YFa, designed as a chimeric peptide between Met 5 -enkephalin-Arg 6 -Phe 7 and FMRFa (Phe-Met-Arg-Phe amide) with structural similarities to dynorphin A, produced KOR-mediated antinociception in rats following i.p administration without producing tolerance [20], although large doses (≥40 mg/kg) were required. Structural modifications, i.e.…”
Section: Development Of Systemically Active Opioid Peptidesmentioning
confidence: 99%
“…A dynorphin A-(1-7) analog stabilized to metabolism, SK-9709 (Figure 1), also exhibited antinociceptive activity following systemic (s.c.) administration (Table 2) [19]. In addition, YFa, designed as a chimeric peptide between Met 5 -enkephalin-Arg 6 -Phe 7 and FMRFa (Phe-Met-Arg-Phe amide) with structural similarities to dynorphin A, produced KOR-mediated antinociception in rats following i.p administration without producing tolerance [20], although large doses (≥40 mg/kg) were required. Structural modifications, i.e.…”
Section: Development Of Systemically Active Opioid Peptidesmentioning
confidence: 99%
“…In our previous study, we designed a chimeric peptide YFa (YGGFMKKKFMRFamide) (32,43) which demonstrated both analgesia and an attenuated morphine tolerance. Similar to YFa in the present study, we designed a chimera of both opioid and NPFF peptides, NPYFa (YGGFMKKKPQRFamide), which contains PQRF (a mammalian endogenous peptide having anti-opioid effects) in place of the FMRF (invertebrate anti-opiate) moiety.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, a corresponding significant increase was observed in expression of DOR1 in brain and spinal cord from day 2 onward which could be attributed to the active opioid motif‐[Y‐(d‐A)‐GFM]‐present in [ d ‐Ala 2 ] YFa. This motif seems to prevent receptor downregulation by inhibiting the binding of endogenous ligands (Law et al, 1985; Bhargava et al, 1993; Lee and Yoburn, 2000; Clarke et al, 2003; Vats et al, 2008). Whereas decrease in DOR1 expression on subsequent days could be the result of desensitization or uncoupling of δ opioid receptors, a phenomenon which is well reported for endogenous as well as exogenous opioid peptide agonists (Burford et al, 1998; Mcconalogue et al, 1999; Horner and Zadina, 2004; Trafton and Basbaum, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Exact receptor specificity of [ d ‐Ala 2 ]YFa was determined using known antagonists namely naloxonazine, naltrindole and nor‐binaltorphimine to selectively antagonize μ,δ and κ opioid receptors, respectively. Rats were treated with previously standardized doses of antagonists (Vats et al, 2008) 5 min prior to i.p. injection of 25.7 μmol/kg [ d ‐Ala 2 ] YFa and tail‐flick latency was measured after 5, 15 and 30 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation